2013
DOI: 10.1158/1078-0432.ccr-12-3529
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase I Trial of the Mitogen-Activated Protein Kinase 1/2 Inhibitor BAY 86-9766 in Patients with Advanced Cancer

Abstract: Purpose: To evaluate the safety, pharmacokinetics, and pharmacodynamics of BAY 86-9766, a selective, potent, orally available, small-molecule allosteric inhibitor of mitogen-activated protein kinase 1/2 in patients with advanced solid tumors.Experimental Design: BAY 86-9766 was administered orally daily in 28-day courses, with doses escalated to establish the maximum-tolerated dose (MTD). An expanded cohort was evaluated at the MTD. Pharmacokinetic and pharmacodynamic parameters were assessed, with extracellul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 29 publications
8
38
0
Order By: Relevance
“…The baseline demographics and disease characteristics of the non-HCC population were broadly consistent with a previous phase I study of refametinib monotherapy (14), although the HCC population comprised slightly more males. Only HCC patients with Child-Pugh A status were enrolled to ensure patients had stable liver function, similar to previous sorafenib trials (22,23).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The baseline demographics and disease characteristics of the non-HCC population were broadly consistent with a previous phase I study of refametinib monotherapy (14), although the HCC population comprised slightly more males. Only HCC patients with Child-Pugh A status were enrolled to ensure patients had stable liver function, similar to previous sorafenib trials (22,23).…”
Section: Discussionsupporting
confidence: 75%
“…Lack of toxicity in cohort 2A (refametinib 5 mg twice daily plus sorafenib 400 mg twice daily) led to escalation with sorafenib 400 mg twice daily as the backbone. The MTD was determined to be refametinib 50 mg twice daily in combination with sorafenib 400 mg twice daily, consistent with the phase I refametinib monotherapy study (14). Overall, daily oral dosing of refametinib plus sorafenib was well tolerated, up to and including at the MTD, with indications of clinical activity, consistent with the phase I study (14).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A similar targeted approach is being taken with the MEK-inhibitor refametinib (BAY 86-9766) in Ras-mutated HCC. Refametinib, a highly selective and potent small molecule allosteric (non-ATP-competitive) inhibitor of MEK 1 and MEK 2, showed potent single agent antitumor activity and acted synergistically in combination with sorafenib in preclinical HCC models, albeit with potential application for only a small subgroup of HCC patients [89][90][91] . Refa- …”
Section: Treatment Of Hccmentioning
confidence: 99%
“…Numerous other early phase clinical trials have reported modulation of pERK in surrogate and tumour tissues following administration of MEK inhibitors [13][14][15]20]. However, differences in assays, tissues and time points used make direct comparisons problematic.…”
Section: Discussionmentioning
confidence: 99%